Efektivitas Platform E-Court dalam Menangani Sistem Peradilan di Pengadilan Agama Kec. Kraksaan - Ilman Abdul Hafihd; Fathullah Rusly; Nina Agus Hariati (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The advancement of information technology has influenced judicial institutions to integrate digital systems into administrative and courtroom processes. The Kraksaan Religious Court has adopted the e-Court platform to enhance judicial service effectiveness and accessibility. This study evaluates the implementation of e-Court at the Kraksaan Religious Court, focusing on its impact on judicial efficiency, encountered challenges, and optimization efforts. Using a qualitative approach with interviews, observations, and document studies, the findings indicate that e-Court has streamlined case administration, improved time efficiency, and reduced costs for justice seekers. However, challenges such as limited technological infrastructure and low public awareness hinder its full potential. This study recommends strengthening public outreach, providing training, and improving technological infrastructure to optimize e-Court implementation at the Kraksaan Religious Court.